Determinan Pemberian ASI Eksklusif di Masa New Normal oleh Ibu Menyusui yang Bekerja dengan Algoritma ID3 - Anisa, Fadhiyah Noor; Yunita, Laurensia; Hidayat, Ahmad (SEULANGA SYSTEM PUBLISHER, 2022)
Exclusive breastfeeding is an important activity in preparing quality generations in the future. Nutrients in the form of sufficient breast milk consumed by infants can affect the growth and development of infants. The source of energy in the form of protein, vitamins and minerals in breast milk is the main source for infants. The 2017 IDHS shows that the coverage of breastfeeding for infants aged < 6 months in Indonesia has generally increased in recent years, reaching 52%. this percentage decreases with the age of the child, for children aged < 1 month the percentage is 67%, this figure decreases to 55% in children aged 2-3 months and decreases to 38% in children aged 4-5 months. One of the obstacles to breastfeeding is a working mother. The purpose of the study was to determine the determinants of breastfeeding during the new normal period by breastfeeding mothers who work with the ID3 algorithm with the method and type of research carried out in this study using a quantitative approach. Quantitative data analysis was carried out in this study using the ID3 Algorithm. The results of the research using the ID3 algorithm found that the determinants of ASIX were obtained from 6 variables: age, education, knowledge, facilities, income and family support, it was found that the knowledge variable was the variable that most influenced the achievement of ASIX in working mothers. As for the income variable, support facilities and education are the accompanying variables. The conclusion of this study is that if the knowledge is good, the variable that becomes the main contributor is income. If there are facilities in the workplace, then the possibility of giving ASIX is achieved, but if there are no facilities in the workplace, family support and the mother's latest education will be seen.